Spontaneous Pneumothorax: A 5-Year Experience - Sousa, C. (2013)
BACKGROUND: Spontaneous pneumothorax (SP) is defined by the presence of air in the pleural space without history of trauma. It is classified as secondary if coexisting with underlying pulmonary disease. Its an entity with considerable incidence and treatment particularities which give reason for a reflection on the subject. We present a 5-year casuistry, characterizing the SP epidemiology, clinical presentation, investigation and therapeutic choices. METHODS: Sixty-six patients were included in the study, corresponding to 93 episodes of SP. RESULTS: We have found male predominance and the mean age was 34.5 years old. In 60.6% of cases there was history of tobacco use; 36.4% of cases were classified as secondary; 30.1% of patients with secondary SP and 21.7% with primary SP recurred; 89.2% had an acute presentation. The most frequent initial symptom was chest pain (90.3%) and 81.7% had diminished breath sounds. In 17.3% it was documented a physical strain associated. We did not identify statistically significant association between the SP occurrence and the variation of the atmospheric pressure, on the first day of symptoms. In 12.9% of episodes the initial treatment option was observation. In most of the episodes the lung totally expanded. However, in 29.1% of the episodes surgical treatment was needed. CONCLUSIONS: Our results are similar to the literature. Some clinical records are incomplete, demanding the implementation of rules to improve knowledge about this matter.